Time course and local distribution of skin exposure of hand and fingers from [68Ga]Ga-DOTA-NOC synthesis using a self-shielded module - Grosser, Oliver Stephan; Wissel, Heiko; Klopfleisch, Maurice; Kupitz, Dennis; Paetzold, Nadine; Pech, Maciej; Kreissl, Michael C. (Nuklearmedizin - NuclearMedicine, 2020)
Aim The study examined the local dose distribution as well as the time course of skin exposure of hand and fingers from [68Ga]Ga-DOTA-NOC synthesis using a self-shielded synthesis module.Methods A compact calibrated electronic dosimeter (ED) with a miniaturized probe was used for real-time measurements of skin dose equivalent Hp (0.07) (reference point: left and right index finger). A time resolved assessment of exposure during radiotracer production was performed. Additionally, thermoluminescence dosimeters (TLD) were used to determine local dose distribution for five different positions (e. g. fingertips). Cumulated Hp (0.07) estimated by ED was analysed and correlated with the measurements obtained by a TLD positioned close to the ED.Results The cumulative skin exposure from the production process measured by ED, was 74.7 ± 32.7 µSv/GBq and 40.1 ± 14.3 µSv/GBq for the right and left hand, respectively. The exposure recorded by the ED was in the average 19.4 % ± 40.0 % (median = 21.3 %) lower compared to the results from TLD. Highest exposure was recorded during synthesis (guided hand: 24.5 ± 12.2 µSv/GBq) and measuring of product yield including preparation of probes for quality control (guided hand: 36.1 ± 12.7 µSv/GBq). The highest local exposure was measured by a TLD close to the tip of the index finger of the guiding hand (range: 773–1257 µS/GBq).Conclusion The chosen methodology using ED, proved to be a good concept for identifying procedure steps with an increased exposure level and to determine the time course of skin exposure and to identify procedure steps for further optimization of handling. Furthermore, miniaturized electronic dosimeters may be used for online surveillance of local exposure rates at hands and fingers.
Keywords: skin exposure; electronic dosimeter; thermoluminescence dosimeters; online surveillance; [68Ga]Ga-DOTA-NOC synthesis